Price Attractiveness and Price Complexity: Why People Prefer Level-Payment Loans - Lu, Yang; Wang, Jian; Li, Chenyang; Huang, Haoya; Zhuang, Xintian (Frontiers in Psychology, 2021)
Recent studies show that the improving sequence effect also exists in a loan context. As consumers have a strong preference for falling loan profiles, banks may consider to offer loans in which the loan repayments concentrate at the beginning of the loan term. In this paper, we examined the correlations between two psychological factors and the evaluation of loan profiles. Our results show that (1) the evaluation of a loan repayment profile is positively correlated with the perceived price attentiveness, and negatively correlated with the perceived price complexity; (2) the TRP( temporal reframing of prices) effect interacts with the improving sequence effect. Specifically, with the introduction of TRP, respondents prefer constant profiles over falling profiles. TRP may explain why level-payment loans are still popular in real world, though the improving sequence effect suggests otherwise.